POLA KOMUNIKASI PADA ORANG TUA YANG MEMILIKI ANAK STUNTING - Febryanti, Ade; Patroni, Rini (JURNAL MEDIA KESEHATAN, 2023)
ABSTRACT Stunting is a national priority program of the Ministry of Health. One of the causes of stunting problems is the lack of communication within the family. Insufficient knowledge of parents about the health and development of children, coupled with busyness, leads to a significant lack of intensity and quality in communication. This deficiency in communication often results in health issues for children, such as stunting in those under two years old. The aim of this research is to understand the communication patterns of parents with stunted children. This study utilizes a qualitative method, with parents of stunted children as informants. The data analysis method employed is depth interviews. The results of the study reveal that the communication pattern applied by the families of Mrs. Nova and Widawati is an authoritarian communication pattern, Mrs. Meimunah and Nurul employ a permissive communication pattern, and Mrs. Dewi adopts a democratic communication pattern. Keywords: Communication, Family, Stunting